Assessing resistance to accept electronic wallets in Egypt - Fouad, Karim Alaaeldin Ahmed; Erakat, Alaa Tarek (Journal of Economic, Administrative and Legal Sciences, 2021)
The purpose of this study is to determine the factors that obstruct the diffusion of electronic wallets in the Egyptian society. As there is great resistance to the use of electronic payment services provided by governmental and private banks, and the insistence of customers to use cash due to the many reasons that were discussed in the research. In spite of this, several countries such as Morocco, Algeria, Malaysia and India, as an example similar to the Egyptian example, have come forward and found many solutions to switch from cash to electronic payment. Nowadays, cell phones have become a fundamental piece of one's everyday life. Users would be able to utilize their Smartphones to make money transactions or online payments by using applications on their phones. There are many mobile wallets, which provide these types of services. Electronic wallets are computerized version of traditional wallets that somebody would carry in their pocket. They offer payment service through which the people/business can receive/send money by smart phones. The current paper highlights the factors that affect Egyptians’ consumer behavior towards electronic wallets, either directly or indirectly and the reasons behind rejecting the idea of replacing cash payments with electronic payments, despite, the global trend to reduce the use of cash especially in the current period of the Coronavirus pandemic. A recent statistic from the Central Bank of Egypt stated that 67% of Egyptians do not have bank accounts, this alarming statistic shows that Egyptians might be uncomfortable dealing with banks, this reflects the level of resistance that Electronic wallet services will face in building familiarity and acceptance with the Egyptian consumers. Through interviews and phone calls with a group of 48 executives and team leaders from government and private banks, in addition to 62 individuals from different age groups- who owned bank accounts in different banks- it was found that the age group from 20 to 40 are the most frequent users of electronic wallets and electronic payment services. Service quality emerged strongly during the study as a variable moderating the acceptance of electronic wallets by customers. Study also indicated that banks’ customers who had concerns about using the electronic wallet for other reasons including making a wrong transaction, refund period, mobile phone coverage when payment is required urgently and on top of this customers had safety concerns and problems dealing with mobile applications. According to 2024 expectations, there is an increase of more than 50% for users of e-wallets for bank account holders, however, through breading familiarity with the concept of electronic wallets and banks investment in a highly secured and user friendly applications percentage could go higher.Recommendations to increase the diffusion rate of e-wallets in the Egyptian society:- A planned and systematic awareness campaign introducing government’s efforts towards using electronic payment services.- Training of the section concerned with technical support to service electronic wallets in all banks to solve all customer problems easily and quickly, which in turn makes the customer satisfied with the service.- Simplifying and facilitating electronic payment applications on mobile phones to facilitate handling by elderly or low-education persons.- Motivating customers to use e-wallets through loyalty program and sales promotions.
Keywords: e-wallet; Customer Satisfaction; Services quality; demographics; pros and cons; education; resistance; online payment